New Synchronization Method For Three-phase Three-wire Pwm Converters Under Unbalanced And Distorted Grid Voltages - Robinson F. de Camargo; Humberto Pinheiro (Eletrônica de Potência)
This paper proposes a new open-loop synchronization method for three-phase three-wire PWM converters connected to the utility grid. It presents a good performance under unbalanced and highly distorted grid voltages. Moreover, it has a better performance in terms of distortions in the synchronization signals if compared with other open-loop methods and it has a good transient performance due amplitude, frequency and angle disturbances. In addition, a frequency adaptation algorithm is proposed for applications where large frequency variations are expected, such as in weak grids. Experimental results using a DSP TMS320F2812 are given to demonstrate the good performance of the proposed synchronization method.